MANAJEMEN SEKOLAH DALAM PEMBENTUKAN KARAKTER SISWA DI MADRASAH TSANAWIYAH BAHRUL ULUM SINGGAHAN TUBAN - Arif Samsurrijal (Al Hikmah: Jurnal Studi Keislaman, 2021)
This paper aimed to describe school management carried out for the process of forming student character in MTs. Bahrul Ulum Singgahan Tuban. The type of research carried out Was qualitative research. The results of the research indicated that there were three processes carried out by schools in the management of character education in MTs. Bahrul Ulum started from the planning, implementation, and evaluation process. The planning process was carried out jointly with the various parties involved (stakeholders) to formulate a plan or program to be implemented, the achievement strategy, and the required budget. Then, in the implementation phase, it appeared that there were several activities that were integrated with the process of inculcating character education, starting from praying together before and after learning, praying dhuhur in congregation, praying dhuha, integration in subjects, extracurricular activities, reciting activities together, and OSIS activities. Then, the evaluation stage was also carried out with the aim of seeing the implementation and non-implementation of the programs that have been implemented, where this was carried out regularly and followed by stakeholders. Keywords: school management, character building, character education, students, Madrasah